Law Enforcement against Platform X Accounts Distributing Pornographic Content: An Analysis of Criminal Liability and Blocking Measures - Makhrom, Wawo Fadholna; Badriyah, Siti Malikhatun (CV. Social Politic Genius (SIGn), 2025)
The proliferation of pornographic content dissemination on Platform X, facilitated by the platform’s permissive internal policies and user anonymity through “alter accounts,” has created an acute juridical conflict with Indonesian positive law. This study aims to analyze the dualism in law enforcement’s response to this phenomenon. Utilizing a normative juridical research method via statute and conceptual approaches, this study examines two pillars of law enforcement: (1) the construction of repressive criminal liability against individual perpetrators, and (2) the preventive administrative authority for account access termination by Komdigi. The results indicate that criminally, the construction of perpetrator liability is dualistic, stemming from Article 27 section (1) of Law Number 1 of 2024 and Article 29 of Law Number 44 of 2008. Administratively, Komdigi’s basis of authority (based on Article 40 section (2b) of Law Number 1 of 2024 in conjunction with Government Regulation Number 71 of 2019) to order the PSE to execute access termination is de jure adequate; however, its de facto effectiveness is hindered by the platform’s internal policies and the difficulty of cross-jurisdictional enforcement. The legal effectiveness analysis finds that overall law enforcement implementation is impeded by legal substance factors (regulatory overlap and legal vacuums regarding new modus operandi such as deepfakes), law enforcement official factors (limitations in forensic human resources), and societal factors (high content demand). Furthermore, a crucial victimological loophole was found where the current legal framework risks criminalizing revenge porn victims.